Risk assessment for diabetes among adult population in urban field practice area of a government medical college in north coastal Andhra Pradesh - Balaga, B. Dhanalaxmi Lolach; Madhavi, K. V. Phani; Madhavi, B. Devi (International Journal Of Community Medicine And Public Health, 2020)
Background: The rising prevalence of diabetes in developing countries is closely associated with industrialization and socioeconomic development. The major determinants of diabetics in these countries are population growth, age structure, and urbanization, prevalence of obesity because of increased intake of junk food, lack of physical activity, and stress among urban dwellers. Diabetes is increasingly concentrated in the urban areas. Hence, the present study was undertaken. To assess the risk of developing diabetes among urban adults >20 years using a Simplified Indian diabetes risk score. Methods: A community based cross-sectional study was carried out in Allipuram, an urban field practice area of Department of Community Medicine, Andhra Medical College, Visakhapatnam. The study was conducted among adults >20 years of age in a sample of 400 adults chosen by simple random sampling technique after obtaining informed consent. The sample size was calculated using 4PQ/L2 with 3% absolute precision (p=9% from previous studies). The study was done for 2 months (October 15th to December 15th 2019). Results: Majority 158 (39.5%) of study participants are at high risk and 198(49.5%) are at medium risk of developing Diabetes in future. Majority 276 (93.3%) of the study participants do not have family history of diabetes. Conclusions: IDRS is a simple, useful and cost-effective tool for prioritizing and identifying medium and high-risk population for developing diabetes and to subject them for screening of diabetes and making screening programs more cost effective in resource limited settings.